2022
DOI: 10.1021/acsbiomaterials.2c00540
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Peri-implantitis: The Quest for a Next Generation of Titanium Dental Implants

Abstract: Titanium and its alloys are frequently the biomaterial of choice for dental implant applications. Although titanium dental implants have been utilized for decades, there are yet unresolved issues pertaining to implant failure. Dental implant failure can arise either through wear and fatigue of the implant itself or peri-implant disease and subsequent host inflammation. In the present report, we provide a comprehensive review of titanium and its alloys in the context of dental implant material, and how surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 333 publications
0
23
0
Order By: Relevance
“…The SEM images show the E. coli are punctured and killed by the surfaces, which is validated by the flat 12-h growth curve of E. coli . The large-area cicada-wing-mimicry antimicrobial surfaces are potentially useful in the food and biomedical industries 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The SEM images show the E. coli are punctured and killed by the surfaces, which is validated by the flat 12-h growth curve of E. coli . The large-area cicada-wing-mimicry antimicrobial surfaces are potentially useful in the food and biomedical industries 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ∼18 million implants are sold annually by different companies [ 110 ]. Despite the high rate of successful osseointegration [ 110 ], dental implants and biomaterials related to tissue regeneration still show early and late complications [ [111] , [112] , 113 ] and it promotes the need for innovation, moreover, the dental market has been reported to be growing quickly, showing a prediction of USD 1.3 billion invested on implant/peri-implantitis treatments and over USD 5.7 billions invested on oral treatments involving biomaterials [ 114 , 115 ].…”
Section: “Bench-to-bedside” – Significant Considerations For Translat...mentioning
confidence: 99%
“…So, the search is ongoing for biomaterials that would meet the requirements without being detrimental to human health. Alternatives to Ti-6Al-4 V alloy include commercially pure titanium (cp-Ti) and β-titanium alloys, which contain only non-toxic chemical elements and demonstrate satisfactory biocompatibility [4,8,[13][14][15]. Moreover, β-alloys are characterised by a lower Young's modulus, more similar to that of human bone, which prevents bone atrophy and the loosening of the implant associated with it [11,13,14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This novel β-alloy has been widely investigated in the literature due to its great promise for biomedicine, a result of its very low Young's modulus, good corrosion resistance, biocompatibility, and relatively high phase stability during further manufacturing processes [18][19][20]. However, for both commercially pure titanium and TNTZ β-alloy, there is still a need to improve their mechanical properties, and surface condition [8,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation